Management of metastatic colorectal cancer: consensus in the Gulf Cooperation Council countries - Bazarbashi Shouki; Alnajjar Abdelsalam; Al Sharm Abdullah; Alshammari Kanan; Al Sherhi Ahmed; Dawoud Emad; Heinemann Volker; Aseafan Mohamed; Chehal Aref; Alghamdi Mohammed; Hamza Dina; Khoury Maroun; et al. (Therapeutic Advances in Medical Oncology)
Colorectal cancer (CRC) represents a major public health challenge globally, particularly in the Gulf Cooperation Council (GCC) countries, where it is identified as the second most prevalent form of cancer. Despite advancements in management strategies, tailored guidelines specific to the Gulf region are lacking. This paper presents consensus recommendations developed by a panel of experts from the GCC countries to address this gap. The guidelines cover epidemiology, screening, biomarkers, and treatment strategies for metastatic CRC. Treatment guidelines emphasize tailored approaches based on tumor characteristics, including sidedness and molecular profiles. Furthermore, the importance of maintenance therapy and emerging biomarkers are discussed. These guidelines aim to improve CRC management and outcomes in the Gulf region.